The Church of All Ages: Generations Worshiping Together - Vanderwell, Howard A. (Rowman & Littlefield Publishers, 2007)
Many congregations today experience collisions between parents who ant to spend time with their children and age-segregated church programming, as well as between the children worshiping in their pews and the increasing number of seniors in the same pew. Among the questions these congregations struggle to address are these: Should we try to hold the generations together when we worship/ Is it even possible? Led by pastor and resource developer Howard Vanderwell, nine writers--pastors, teachers, worship planners, and others serving in specialized ministries--offer their reflections on issues congregational leaders need to address as they design their worship ministry. In addition, numerous sidebars illustrate the diversity of practices in the church today. Contributors do not propose easy answers or instant solutions. Rather, they guide readers as they craft ministries and practices that fit their own community, heritage, and history. Each chapter includes questions for reflection and group discussion, and an appendix provides guidelines for small group use. The thread that connects these varied contributions is the belief that there is no greater privilege for Christians than worshiping God, and there is no better way to do that than as an intergenerational community in which all are important and all encourage and nurture the faith of the others.